1995
DOI: 10.2134/agronj1995.00021962008700060027x
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Rate of Ethephon Application to Two‐Row and Six‐Row Spring Barley

Abstract: Ethephon (2‐chloroethyl phosphonic acid) reduces lodging in barley (Hordeum vulgare L.) by shortening straw, but the optimal rate and growth stage of application, both of which may interact with cultivar and environment, are unclear, especially for two‐row barley in North America. Field studies in Quebec in 1985 and 1986 evaluated the response of ‘Leger’ six‐row and ‘Birka’ two‐row barley to ethephon applied at varying rates, growth stages, and times of day. The two‐row cultivars Rodeo and Micmac were also inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Earlier studies suggested various HI values ranging from 0.4 to 0.6 for maize and barley (e.g. Kiniry et al, 1997;Bridger et al, 1995), but it is not easy to identify a suitable value for a given study area. The value depends on many factors such as cultivars and management practices.…”
Section: Agb Estimation With Landsat Images and Regional Crop Informamentioning
confidence: 99%
“…Earlier studies suggested various HI values ranging from 0.4 to 0.6 for maize and barley (e.g. Kiniry et al, 1997;Bridger et al, 1995), but it is not easy to identify a suitable value for a given study area. The value depends on many factors such as cultivars and management practices.…”
Section: Agb Estimation With Landsat Images and Regional Crop Informamentioning
confidence: 99%
“…In the breeding experiment of Boukerrou and Rasmusson (1990), the mean HI for commonly grown cultivars was 0.48. Bridger et al (1995) performed an experiment in preventing lodging with the application of ethephon and found a mean HI of 0.48 for controls to which no ethephon was applied. Bridger et al (1995) performed an experiment in preventing lodging with the application of ethephon and found a mean HI of 0.48 for controls to which no ethephon was applied.…”
Section: Crop Harvest Indicesmentioning
confidence: 99%
“…Jedel and Helm (1994) examined the agronomic traits of barley in western Canada and found a HI of 0.52 for six-rowed cultivars and 0.50 for two-rowed cultivars. Bridger et al (1995) performed an experiment in preventing lodging with the application of ethephon and found a mean HI of 0.48 for controls to which no ethephon was applied. Nedel et al (1993) obtained a mean HI of 0.52 in a study of the effects of nitrogen fertilization on barley yield and malting quality, at nitrogen application rates up of 60 kg/ha.…”
Section: Crop Harvest Indicesmentioning
confidence: 99%
“…Ethephon treatment can result in a reduced barley harvest index. While ethephon reduces lodging, it also results in incomplete spike emergence and reduced tiller survival and, consequently, reduced grain weights (Bridger et al 1995). Harvest index is influenced by interactions among rainfall patterns, N fertilization and grain-filling temperature (Gonzales-Ponce et al 1992).…”
Section: Harvest Indexmentioning
confidence: 99%
“…Harvest index and yield were shown to decrease with increased water deficit (Salam et al 1991), saline irrigation (Ahmed et al 1993) and interference by quackgrass (Pageau and Tremblay 1995). Decreased yield generally occurs where harvest index is reduced (Bridger et al 1995). However, growing conditions may be such that yield and total biomass production are increased but harvest index is reduced (Jedel and Helm 1992).…”
Section: Harvest Indexmentioning
confidence: 99%